Effect of Hydrogen Content and Bonding Environment on Mechanical Properties of Hydrogenated Silicon Films Deposited by High-Frequency PECVD Process. (17th July 2012) - Gope, Jhuma; Kumar, Sushil; Parashar, A.; Dayal, S.; Rauthan, C. M. S.; Srivastava, P. C.
Abstract : The mechanical properties of hydrogenated silicon thin films deposited using high-frequency PECVD process were studied, which certainly have importance for optoelectronic devices particularly for getting stability and long operating lifetime in harsh conditions. Nanoindentation technique was used to measure the load versus displacement curves, hardness ( H ), elastic modulus ( E ), plastic resistance parameter ( H/E ), elastic recovery (ER), and plastic deformation energy (U r ), while laser scanning stress measurement setup was used to measure the intrinsic stress of these films. The concentration of bonded hydrogen in these films was found in the range of 3.6 to 6.5 at. % which was estimated using integrated intensity of IR absorption peak near 640 cm − 1 . Dependence of mechanical properties of these films on hydrogen content and bonding environment has been investigated. The film containing minimum hydrogen content (3.6%) shows the maximum elastic recovery (52.76%) and minimum plastic deformation energy (3.95 × 10 − 10 J). Surface roughness measured by AFM was found to decrease with the increase in hydrogen content in the film. The dependency of stress on the plasma frequency and applied power has also been discussed.